Growth, Survival Rate and Feed Conversion Ratio of Juveniles of Macrobrachium rosenbergii (de Man) Fed with Farm made and Commercial Feeds - B., Madhusoodana Kurup; B., Hari (Fishery Technology, 2025)
Feeding trial was conducted in M. rosenbergii to compare efficiency of the farm made feed (diet FMF) with commercial feeds like CP feed (diet A), Higashi feed (diet B), and Rosen feed (diet C). Dried clam meat was used as the control feed (diet D). Water stability of FMF is found well comparable with the above feeds. Higher specific growth rate was recorded in diet FMF (2.02) that did not vary significantly (p>0.05) among the dietary treatments except in diet D (1.15). Higher survival was recorded in diet FMF (91.07%) followed by diet A (90.48%), diet B (89.68%) and diet C (82.14%) while the survival of the juvenile of M. rosenbergii fed with control diet (37.5%) was significantly (p